Strategi Pemasaran Kacang Asin Kelompok Wanita Tani Sinar Rejeki Desa Jumpai, Kecamatan Klungkung, Kabupaten Klungkung - NI MADE HENY SUANDANI; DWI PUTRA DARMAWAN; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
The Marketing Strategy Salted Peanut Women Farmers Group Sinar Rejeki in Jumpai Village, Klungkung District, Klungkung RegencyThe marketing strategy is a fundamental statement about the impact expected to be achieved in terms of demand on the specified target market. Oriented marketing strategy to create added value for customers and establish cooperative relationships with customers. The marketing strategy has a broad scope in the field of marketing include the strategy in the face of competitors, pricing strategy, product strategy, and so on. This study aims to determine the strengths, weaknesses, opportunities, threats, and strategies that must be done by the Women Farmers Group Sinar Rejeki in Jumpai village, Klungkung District, Klungkung Regency on the marketing of salted peanuts. This research was conducted in November to June 2016 held at the Women Farmers Group Sinar Rejeki in Jumpai Village, Klungkung District, Klungkung Regency. Source of research data from primary and secondary data. The key informants of this study classified a key informant for the weights (Women Farmers Group Sinar Rejeki and Agriculture, Plantation and Forestry Klungkung) and key informants for the rating (customers and competitors). This method of analysis used in this research is the analysis of the enterprise environment consisting from IFAS matrix (internal strategy factors) and matrix analysis EFAS (external strategic factors), and SWOT matrix. The analysis showed that the matrix IFAS earn a score of 2,9 and EFAS matrix given a score of 3,55.